A Critical Review On The Development And Function Of Hridaya W.S.R. To Ayurvedic And Modern Embryological Literature - Kumari, Nitu; Priyanka, Priyanka; Gupta, S.S. (Journal of Neonatal Surgery, 2025)
The heart (Hridaya) holds a position of vital importance in both Ayurvedic and modern biomedical sciences. In Ayurveda, Hridaya is conceptualized not merely as an anatomical structure but as a fundamental seat of life, integrating physiological, psychological, and spiritual dimensions. It is regarded as the abode of Prana (vital life force), Ojas (vital essence or immunity), and Mana (mind), playing a pivotal role in sustaining consciousness, circulation, and vitality. Conversely, modern science describes the heart as a muscular organ of mesodermal origin, functioning as a central pump of the circulatory system and one of the first organs to develop during embryogenesis. This critical review explores the integrative concept of Hridaya by correlating its Ayurvedic understanding—derived from classical texts such as the Charaka Samhita and Sushruta Samhita—with the scientific processes of cardiac embryology and physiology described in contemporary medical literature. The article aims to investigate both the ontogeny (developmental origin) and the functional aspects of Hridaya from these two knowledge systems. A comparative analysis highlights commonalities, such as the early development and vital function of the heart, while also acknowledging philosophical and epistemological differences. By examining Hridaya through the dual lenses of Ayurvedic Garbha Sharira (embryology) and modern cardiogenesis, this review bridges traditional metaphysical insights with evidence-based developmental biology. It ultimately provides a holistic and enriched perspective on the origin, structure, and functional significance of the heart, inviting further interdisciplinary research into Ayurvedic anatomy and modern embryology